Ergonomic analysis for the assessment of the risk of work-related musculoskeletal disorder in forestry operations - Raimondo Gallo; Fabrizio Mazzetto (Journal of Agricultural Engineering, 2013)
The risk to run into a Work-Related Musculoskeletal Disorder (WMSD) is very high when operating in the primary sector. As a matter of fact the professional illnesses related to the WMSD in Italy are increasing. Nowadays the assessment of the WMSD in the primary sector is performed mainly in the agricultural sector, considering different agronomical activities; for the forestry sector, only few documents reported an ergonomic evaluation. The lack of available information on this topic in the forestry sector, as well as the similarity with the agricultural sector, drives the interest to the assessment of the conditions that expose workers to WMSD risks in forestry operations. Four different assessment approaches were applied in this study. These tools permitted to classify which are the exposures and if there is the presence of WMSD risk for forest operators. The approaches are respectively the OCRA checklist and the RNLE equation, both recognized as ISO standards, as well as OWAS and REBA, recommended by ISO standards. The first approach focusses on the risk due to repetitive and stressed movements, while the second evaluates the risk of injures due to the manual movement of loads. Meanwhile OWAS and REBA detect the possibility of injures due to wrong postures during the work. These approaches were applied for the cutting operations with chainsaw. Since the evaluation requires high levels of attention and also because it was necessary to gain a good level of safety for the surveyor, a digital camera was used to film the operative activities. Then, the movies were analysed in office. Aim of the research is to analyse if it is possible to apply the approaches suggested by ISO standards in order to assess the most dangerous activities that, when not properly carried out, could be the cause of WMSD in forestry operations. The study showed that during the use of the chainsaw the index of risk of professional injures was overpassed several times, compromising the operator’s safety.